The problems facing the agricultural sector in Nigeria and the prospect of Muzara’ah and supply chain model - Oladokun , Nafiu Olaniyi; Larbani, Moussa; Mohamed, Mustafa Omar (Emerald Group Publishing, 2015)
Purpose – The purpose of this paper is to develop a Muzara’ah–supply chain model for the purpose of enhancing agricultural financing and productivity in Nigeria.